2022
DOI: 10.1002/cam4.5277
|View full text |Cite
|
Sign up to set email alerts
|

Study of SOX combined with intraperitoneal high‐dose paclitaxel in gastric cancer with synchronous peritoneal metastasis: A phase II single‐arm clinical trial

Abstract: Background: Intraperitoneal paclitaxel is proved to be efficient for peritoneal metastasis of gastric cancer. It remains uncertain the efficacy and safety of the triplets regimen which combined intraperitoneal high-dose paclitaxel with systemic SOX in gastric cancer patients with peritoneal metastasis. This study aimed to evaluate the efficacy and safety of intraperitoneal administration of high-dose paclitaxel, intravenous oxaliplatin and S-1 in patients with peritoneal metastatic gastric cancer.Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The JGCA classification evaluates the presence of positive cytology (C0 or C1) and the presence of macroscopic peritoneal metastases (P0 or P1) 36 , whereas the PCI scores the extent of macroscopic peritoneal disease in 13 pelvic–abdominal regions 37 . Three studies used the JGCA classification 21 , 27 , 29 , 14 studies reported the PCI score 13–18 , 22 , 25 , 30–35 and 5 studies used both methods 19 , 23 , 24 , 26 , 28 . One study did not report a classification for peritoneal metastases 20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The JGCA classification evaluates the presence of positive cytology (C0 or C1) and the presence of macroscopic peritoneal metastases (P0 or P1) 36 , whereas the PCI scores the extent of macroscopic peritoneal disease in 13 pelvic–abdominal regions 37 . Three studies used the JGCA classification 21 , 27 , 29 , 14 studies reported the PCI score 13–18 , 22 , 25 , 30–35 and 5 studies used both methods 19 , 23 , 24 , 26 , 28 . One study did not report a classification for peritoneal metastases 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies defined peritoneal disease as macroscopic peritoneal disease (that is, P1 on JGCA classification or PCI ≥ 1) 13 , 15–19 , 22 , 24–26 , 28 , 29 , 31–35 . The remaining six studies defined peritoneal disease as positive cytology in ascites or macroscopic peritoneal disease 14 , 20 , 21 , 23 , 27 , 30 . In 816 patients the peritoneal disease stage was described, of whom the majority (97%) had macroscopic peritoneal disease; 3% of patients had positive cytology only.…”
Section: Resultsmentioning
confidence: 99%
“…High-dose intraperitoneal paclitaxel (80 mg/m 2 ) in 3-week cycles combined with oxaliplatin and S-1 showed comparable results with a 1-year overall survival rate of 82% and a median overall survival of 16.9 months [72]. In patients receiving intraperitoneal paclitaxel, several prognostic factors were discovered.…”
Section: Gastric Cancermentioning
confidence: 93%
“…Table 2 presents an overview of the reported portrelated complications in Phase II and Phase III studies [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. Moreover, two retrospective studies focused on the complications of intraperitoneal access.…”
Section: Intraperitoneal Access Portmentioning
confidence: 99%
“…This drug also inhibits the effects of other factors on the microtubule system and, together with the stable binding of microtubule proteins, eventually induces apoptosis ( Liu et al, 2017a ). In clinical applications, paclitaxel has shown good efficacy in treating non-small cell lung cancer ( Hoang et al, 2012 ), breast cancer ( Manhas et al, 2022 ), gastric cancer ( Tu et al, 2022 ), nasopharyngeal cancer ( Xia et al, 2022 ), ovarian cancer ( Kong et al, 2023 )and cervical cancer ( Yasunaga et al, 2022 ), particularly for drug-resistant tumors ( Song et al, 2018 ; Kawiak et al, 2019 ). Although the therapeutic efficacy of paclitaxel in glioma has been confirmed, its therapeutic mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%